Cesare Cases e la didattica della letteratura - Santarone, Donatello (L'ospite ingrato, 2024)
The essay examines a 1979 text by Cesare Cases in which the great Germanist argues, through ironic and pungent prose, against the technocratic approach to the analysis and teaching of literature. In this approach Cases sees the literary equivalent of the division of labour and the fragmentation of the subject, which are the foundation of the capitalist mode of production. From a theoretical methodological point of view, the essay underlines the importance that have for Cases Marxist historicism, the Hegelian-Marxian and Lukácsian category of “totality”, as an “attempt to reconnect the particular to the universal”, but always accompanied by a solid critical-philological foundation.